New Solutions of Gardner's Equation Using Two Analytical Methods - Ghanbari, Behzad; Baleanu, Dumitru (Frontiers in Physics, 2019)
me exact solutions to the Gardner’s equation are obtained with the help of two analytical methods including the generalized exponential rational function method and a Jacobi elliptical solution finder method. A set of new exact solutions containing four parameters is reported. The graphical interpretation of the solutions is depicted. Mathematica software is used to perform the computations and simulations. The suggested techniques can be used to another sort of real-world models from science and engineering.